Nutrition Status And Neuropsychiatric Disorders In Indonesian Childhood Lupus: Experience At A Single Tertiary Referral Center - Hikmah, Zahrah; Endaryanto, Anang; Sutawan, Ida Bagus Ramajaya; Wulandari, Desy (Universitas Airlangga, 2024)
NPSLE diagnosis is still challenging because of many SLE-related and non-SLE-related processes that can be presented in patient. The report of NPSLE in Indonesia is still limited. This study aim to describe the clinical features, nutrition status, and laboratory characteristics of Neuropsychiatric Systemic Lupus Erythematosus (NPSLE) and compared to non NPSLE case in Indonesian children. The study is a retrospective cohort study. Data were collected from the complete medical record of Juvenile Systemic lupus Erythematosus (jSLE) patients 2016 - 2020 at the Allergy Immunology Outpatient clinic at Dr. Soetomo General Academic Hospital. We include all patients with ages ranging from age 0-18 years old with a diagnosis of Systemic lupus Erythematosus (SLE). The diagnosis fo SLE based on American College of Rheumatology (ACR) criteria 1997 and Neuropsychiatric (NP) manifestations were classified using the standardized nomenclature and case definitions for the 19 NP manifestations linked to SLE developed in 1999 by the ACR ad hoc Committee. Disease activity SLE was defined according to the American Mexican-Systemic Lupus Erythematosus Disease Activity Index (Mex-SLEDAI) criteria. Statistical analysis conducted in this study was descriptive analysis, paired T-test (NPSLE vs. non-NPSLE as the dependent variable), Fischer exact test, and Pearson Chi-square test using SPSS ver. 21. A total of 90 patients with juvenile SLE were enrolled, but only 71 patients were eligible as participants with complete medical records obtained. Mex-SLEDAI score was significantly higher on NPSLE compared to non-NPSLE (p=0.001).